Entropy production and mixed convection within trapezoidal cavity having nanofluids and localised solid cylinder - Ishak M.S.; Alsabery A.I.; Hashim I.; Chamkha A.J. (Nature Research, 2023)
The entropy production and mixed convection within a trapezoidal nanofluid-filled cavity having a localised solid cylinder is numerically examined using the finite element technique. The top horizontal surface moving at a uniform velocity is kept at a cold temperature, while the bottom horizontal surface is thermally activated. The remaining surfaces are maintained adiabatic. Water-based nanofluids (Al 2O 3 nanoparticles) are used in this study, and the Boussinesq approximation applies. The influence of the Reynolds number, Richardson number, nanoparticles volume fraction, dimensionless radius and location of the solid cylinder on the streamlines, isotherms and isentropic are examined. The results show that the solid cylinders size and location are significant control parameters for optimising the heat transfer and the Bejan number inside the trapezoidal cavity. Furthermore, the maximum average Nusselt numbers are obtained for high R values, where the average Nusselt number is increased by 30% when R is raised from 0 to 0.25. 2021, The Author(s).